Electromagnetic measurements in the near field - Bienkowski, Pawel (SciTech series on electromagnetic compatibility., 2012)
The book reviews developments in the following fields: electromagnetic measurement; near field; far field; electric field measurement; magnetic field measurement; power density measurement; directional pattern synthesis; and photonic EMF measurement.